The association of the 'additional height index' with atopic diseases, non-atopic asthma, ischaemic heart disease and mortality: a population-based study. Issue 2 (28th February 2014) - Fenger, R V; Vidal, C; Gonzalez-Quintela, A; Husemoen, L L N; Skaaby, T; Aadahl, M; Linneberg, A
Abstract : Objective: Intrauterine growth has been associated with atopic conditions. Growth and adult height have been associated with cardiovascular disease, cancers and mortality but are highly genetic traits. The objectives of the study were as follows: first, to define a height measure indicating an individual's height below or above that which could be expected based on parental height (genetic inheritance) and growth charts. It was named 'the additional height index' (AHI), defined as (attained—expected) height; second, to investigate possible associations of AHI with atopic versus non-atopic health outcomes and with ischaemic heart disease (IHD) and IHD mortality. Design: General population-based study. Setting: Research centre. Participants: A random sample of 2656 men and women living in greater Copenhagen took part in the MONICA10 study (the Danish monitoring trends and determinants of cardiovascular disease). In total, 1900 participants with information of parental height were selected. Outcome measures: Atopic sensitisation (serum IgE), questionnaire information of atopic dermatitis, rhinoconjunctivitis, asthma or wheezing, and registry-based diagnoses of IHD/IHD mortality from National Registries. Results: Increasing levels of AHI were inversely associated with non-atopic asthma, non-atopic wheezing, IHD and IHD mortality (IHD-all). For one SD increase of AHI, the OR or HR with CI in adjusted analyses was non-atopic asthma OR=0.52 (0.36 to 0.74), non-atopic wheezing OR=0.67 (0.51 to 0.89), and IHD-all HR=0.89 (0.78 to 1.01). The level of AHI was higher among individuals with atopic dermatitis, allergic rhinoconjunctivitis and atopic sensitisation (all p values <0.001) compared with individuals without those conditions; however, the associations were not confirmed in adjusted analyses. Conclusions: Individuals with childhood conditions that led them to attain tallness higher than expected from their parents' height may be at lower risk of non-atopic asthma/wheeze and IHD/IHD mortality but possibly at higher risk of atopic conditions. The measure of tallness below or above the expected height could be a sensitive alternative to normal height in epidemiological analyses.